2017
DOI: 10.1080/15476286.2016.1267074
|View full text |Cite
|
Sign up to set email alerts
|

How is Herstatin, a tumor suppressor splice variant of the oncogeneHER2, regulated?

Abstract: The human epidermal growth factor receptor 2 (HER2)/receptor tyrosine-protein kinasebB-2 (ERBB2) is overexpressed in 20-30% of breast tumors leading to faster growing and more aggressive tumors. Alternative splicing generates a functionally distinct HER2 variant called Herstatin, which is produced by the inclusion of intron 8. Herstatin acts as a tumor suppressor by effectively blocking HER2 activity and cell proliferation, while promoting apoptosis. In the present study we investigated HER2 pre-mRNA regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…This finding is made less surprising by the relatively large amounts of protein present at the membrane, perhaps implying it can bind to the cellular membrane or dimerize with other family members with the novel C-terminus. Data suggests that HER2-I12 may behave differently to the two previously identified truncated HER2 splice variants, Herstatin and P100; both block downstream signalling likely by binding to HER2-WT receptors at the cell membrane to halt dimerization (Jackson et al 2013 ; Silipo et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is made less surprising by the relatively large amounts of protein present at the membrane, perhaps implying it can bind to the cellular membrane or dimerize with other family members with the novel C-terminus. Data suggests that HER2-I12 may behave differently to the two previously identified truncated HER2 splice variants, Herstatin and P100; both block downstream signalling likely by binding to HER2-WT receptors at the cell membrane to halt dimerization (Jackson et al 2013 ; Silipo et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Herstatin is a secreted 'auto-inhibitor' with intron 8 retention which causes truncation, producing a HER2 protein with only the extracellular regions and a novel C-terminus (Silipo et al 2017). Herstatin can still bind to a HER2-WT receptor which stops HER2-WT homo-or hetero-dimerization and so blocks downstream signalling (Azios et al 2001;Koletsa et al 2008;Hu et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…6G ). Significantly, ECD KD led to an increase in the expression of herstatin, a tumor suppressor splice variant ( 58 60 ), but a reduction in the expression of the Δ16HER2 variant, a prooncogenic splice variant ( 57 , 61 , 62 ). Taken together, we demonstrate transcriptional regulation of ErbB2 and its splice variants by ECD.…”
Section: Resultsmentioning
confidence: 98%
“…Such different pattern of expression of these two variants might imply specific roles for them which should be assessed in future studies. Evidence from protein coding genes has shown that alternative splicing can change oncogenic role of a protein to tumor suppressor role 15,16. However, data regarding the presence of such contrary functions of splice variants of lncRNA are scarce due to the significant difference in splicing dynamics between protein coding and lncRNA genes and lower completed splicing index for lncRNAs in the total chromatin fraction 17.…”
Section: Discussionmentioning
confidence: 99%